DETEKSI DINI KEBUNTINGAN PADA SAPI BALI MENGGUNAKAN ASAM SULFAT (H2SO4). - suparmin fathan (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2018)
The purpose of this study was to determine the appropriate dosage, time and method of diagnosing pregnancy in Balinese cattle using a mixture of urine and aquadest which was reacted with Sulfuric Acid (H2SO4). This research was conducted in February - March 2018 in Bongo village, Wonosari sub-district, Boalemo Regency, Gorontalo Province. The material used is urine urine samples, which have been artificially inseminated. Concentrated sulfuric acid (H2SO4) of 0.3 ml, 0.5 ml, 0.7 ml, 0.9 and 0.11 ml (according to treatment). The variables observed were fluorescence gas in solution, change in color of solution, time of change in solution. Data were analyzed using unidirectional variance analysis. The results showed pregnancy detection in Balinese cows who had been on IB in each treatment gave a very significant effect (P 0.01. The results of the BNT test revealed that the age of 6 days had the fastest time in detecting pregnancy with ± 6 seconds, at age 11 and 16 days have the fastest time in detecting pregnancy, with an average time of ± 5 seconds the pregnancy can be detected.